Elevated SerpinB2 regulates MUC5AC expression via STAT6 signaling in nasal epithelial cells in allergic rhinitis - Li, Jing; Cui, Qianbo; Li, Zhipeng; Zhu, Ying; Wang, Jing; Chen, Wei (Frontiers in Immunology, 2025)
BackgroundSerpinB2 is expressed in airway epithelial cells in nasal polyps and asthma in association with Type-2 inflammation. Allergic rhinitis (AR) is similarly associated with Type-2 inflammation and mucus hypersecretion. MUC5AC has been reported to be regulated by IL-13 in nasal epithelial cells (NECs). This study aimed to evaluate SerpinB2 expression in AR and determine whether SerpinB2 regulates MUC5AC via STAT6 signaling.MethodsSerpinB2 gene expression in single-cell RNA sequencing databases was analyzed through bioinformatics approaches. SerpinB2 and MUC5AC expression levels were evaluated in intermittent or persistent AR patients and healthy controls (HC). Colocalization of SerpinB2 and MUC5AC was assessed by immunofluorescence. Fresh NECs were cultured at air-liquid interface with or without IL-13, SerpinB2 Dicer-substrate short interfering RNAs (DsiRNAs) transfection, exogenous SerpinB2, and pSTAT6 inhibitors. SerpinB2, MUC5AC, and STAT6 were analyzed using qRT-PCR, Western blot, immunofluorescence, and ELISA.ResultsSerpinB2 expression was significantly increased in both intermittent and persistent AR compared to normal mucosa from HC. SerpinB2 correlated with MUC5AC expression and colocalized with MUC5AC in NECs from AR patients. In primary NECs in vitro, IL-13 induced both SerpinB2 and MUC5AC expression. Knockdown or overexpression of SerpinB2 correspondingly decreased or increased MUC5AC expression in NECs. STAT6 inhibition similarly reduced SerpinB2-induced MUC5AC expression.ConclusionsSerpinB2 is upregulated in AR NECs and contributes to MUC5AC expression through STAT6 signaling pathway activation. Therefore, targeting SerpinB2 may have therapeutic value in treating AR patients.